Performance of LOSO models. - Ioana Duta (18462981) (2025)
Boxplot of AUC values resulting from the testing, on each site in turn, of models trained on all but one site. Both internal and external performance is shown. Internal performance was higher in 3 sites (internal median 0.93, external median 0.89). In the other two, AUC values displayed a larger range (internal median 0.92, range 0.04; external median 0.96, range 0.05). AUC = area under receiver operating curve. Internal performance = performance on sites included in training data. External performance = performance on the site that was not included in training data. Central line is median; lower edge of the box indicates first quartile, upper edge of the box indicates third quartile; points are extreme performance scores.